Candida albicans aspects of binary titanium alloys for biomedical applications. Issue 2 (25th January 2020) - Chen, Shuyang; Tsoi, James K H; Tsang, Peter C S; Park, Yeong-Joon; Song, Ho-Jun; Matinlinna, Jukka P
Abstract: Titanium and its alloys are widely used in biomedical devices, e.g. implants, due to its biocompatibility and osseointegration ability. In fact, fungal ( Candida spp.) infection has been identified as one of the key reasons causing the failure of the device that is inevitable and impactful to the society. Thus, this study evaluated the surface morphology, surface chemical composition and Candida albicans adhesion on specimens of 16 binary Ti-alloys (∼5 wt% of any one of the alloy elements: Ag, Al, Au, Co, Cr, Cu, Fe, In, Mn, Mo, Nb, Pd, Pt, Sn, V and Zr) compared with cp-Ti, targeting to seek for the binary Ti-alloys which has the lowest C. albicans infection. Candida albicans cultures were grown on the specimens for 48 h, and colony forming units (CFUs) and real-time polymerase chain reaction (RT-PCR) were used to evaluate the biofilm formation ability. Scanning electron microscopy and confocal laser scanning microscopy confirmed the formation of C. albicans biofilm on all specimens' surfaces, such that CFU results showed Ti-Mo, Ti-Zr, Ti-Al and Ti-V have less C. albicans formed on the surfaces than cp-Ti. RT-PCR showed Ti-Zr and Ti-Cu have significantly higher C. albicans DNA concentrations than Ti-Al and Ti-V ( P < 0.05), whereas Ti-Cu has even showed a statistically higher concentration than Ti-Au, Ti-Co, Ti-In and Ti-Pt ( P < 0.05). This study confirmed that Ti-Mo, Ti-Zr, Ti-Al and Ti-V have lower the occurrence of C. albicans which might be clinically advantageous for medical devices, but Ti-Cu should be used in caution.